Combinatorial protection of cochlear hair cells: not too little but not too much - Kurabi, Arwa; Pak, Kwang; Lee, Eun Jung; Ryan, Allen F. (Frontiers in Cellular Neuroscience, 2024)
Background A number of drugs are toxic to the cochlear sensory cells known as hair cells (HCs), resulting in hearing loss. Treatment with survival-promoting growth factors, antioxidants, and inhibitors of cell death pathways or proteinases have been shown to reduce HC damage in in vivo and/or in vitro animal models. Conversely, translation to humans has often been disappointing. This may be due to the complexity of intracellular damage processes. We hypothesized that combining treatments targeting different cellular processes would be more effective. Methods Using an in vitro model of gentamicin ototoxicity for murine cochlear hair cells, we screened all 56 possible combinations of inhibitors targeting five different cell damage mechanisms, plus the activator of one cell survival pathway, each of which have been shown to be singly effective in preventing HC loss in experimental studies. A high dose of gentamicin (200 μM) was used over three days in culture. All compounds were added at a dosage below that required for significant protection in the assay, and only this single dose was then employed. This was done so that we could more easily detect interactive, as opposed to additive, effects. Results Increasing protection of hair cells was observed as combinations of compounds were increased from two to four factors, although not all combinations were equally protective. The optimal combination of four compounds consisted of an anti-oxidant, an apoptosis inhibitor, an autophagy inhibitor and a protective growth factor. Increasing the number of factors to five or six resulted in decreased protection. Conclusion The results support the hypothesis that targeting multiple cellular damage or survival pathways provides more an effective hair cell protection approach. The results help to identify critical interactions among the cellular processes that operate in gentamicin ototoxicity. They also suggest that inhibiting too many biological processes impairs functions critical to HC survival, resulting in decreased protection.